The Palgrave handbook of leadership in transforming Asia - Muenjohn, Nuttawuth; McMurray, Adela (Palgrave Macmillan, 2017)
This handbook provides a comprehensive overview and evaluation of the variety of organizational leadership issues within the Asian region. It highlights the relationship between leaders and their followers, and the complexity of leadership research and practices in Asian transformational economies. Covering a wide range of contexts and perspectives, the chapters are based on empirical studies with evidence-based findings that can be used as case studies for academics and practitioners. The handbook makes significant contributions to leadership theory including practice and assists international researchers, practitioners and students in understanding the influence of the Asian culture and its impact on leadership.- Resumé vydavatel
Keywords: řídící práce; úspěch v podnikání; mezinárodní podnikání; leadership; success in business; international business; Asie; Asia; elektronické knihy; kolektivní monografie; příručky; electronic books; collective monographs; handbooks and manuals